Tea in Health and Disease - Dou, Q. Ping (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Tea, made from the leaves of the Camellia senenisis plant, is the second most consumed beverage worldwide after water. Accumulating evidence from cellular, animal, epidemiological and clinical studies have linked tea consumption to various health benefits, such as chemoprevention of cancers, chronic inflammation, heart and liver diseases, diabetes, neurodegenerative diseases, etc. Although such health benefits have not been consistently observed in some intervention trials, positive results from clinical trials have provided direct evidence supporting the cancer-protective effect of green tea. In addition, numerous mechanisms of action have been suggested to contribute to tea's disease-preventive effects. Furthermore, effects of the processing and storage of tea, as well as additives on tea's properties have been investigated.